Stress and anxiety among physicians and nurses in Romania during the COVID-19 pandemic - Romina-Marina Sima; Octavian-Gabriel Olaru; Anca Cazaceanu; Cristian Scheau; Mihai-Traian Dimitriu; Mihai Popescu; Liana Ples (Journal of Mind and Medical Sciences)
Objective. This study aimed at identifying the stress and anxiety levels among physicians and nurses working in Romanian hospitals during the COVID-19 pandemic. Methods and Results. We conducted an online survey with a questionnaire completed by 169 healthcare providers aged between 25 and 69 years from COVID and non-COVID hospitals. There were 87.6% physicians and 12.4% nurses, with 61.5% women and 38.5% men. Clinicians experienced high levels of stress in 2.7% of the cases, medium stress in 68.9% of the cases, and low stress in 28.4% of the cases. Women experienced more stress (2.9% high level, 66.3% medium level) than men (1.5% high level, 64.6% medium level), while men are more anxious (73.8% high level, 26.2% medium level) than women (63.6% high level, 33.7% medium level). In both COVID and non-COVID healthcare providers, the stress score directly correlates with the anxiety score. Overall, during this period, the responders felt stressed and anxious (p=0.001). Conclusions. The COVID-19 pandemic is a strong reason for increased stress and anxiety among physicians and nurses. Men are more anxious and women more stressed. The stress and anxiety scores are different according to the hospital type.